Resource Availability, Awareness and Barriers to Inclusive Physical Activity and Sports For Special Needs Persons in University of Ilorin - Sangodeyi, Oluwatosin Adejare; Dominic, Olufunmilola Leah; Adeoye, Sikiru Adewale; Alabi, Afusat Titilayo; Chukwudo, Donatus Udochukwu (International Journal of Human Kinetics, Health and Education, 2025)
The study investigated resource availability, awareness and barriers to inclusive Physical Activity and Sports for Special Needs Persons (SNPs) in University of Ilorin. Descriptive research design of survey type was used for the study. Purposive sampling technique was used to select 32 special-needs students based on their availability and accessibility. A validated questionnaire named rresource availability, awareness and barriers to inclusive physical activity and sports questionnaire (RAABIPASQ) with a reliability coefficient of .74 was used for data collection. The data collected were analysed using descriptive statistics of frequency counts, percentage and decision mean. Findings of the study revealed that; only halls accessibility 17 (53.1%) and co-curricular activities encouragement 18 (56.3%) are available resources; there is level of awareness for inclusive PA and sports (decision mean >2.50); there are barriers militating against the inclusive PA and sports (with decision means >2.50); there is high level of awareness on implications of disability acts towards inclusive PA and Sports (decision mean >2.50) among (SNPs) in University of Ilorin. It was concluded that; majority of the resources required for inclusive PA and Sports are not available; there is awareness for inclusiveness in PA and Sports; there are barriers militating the inclusive PA and sports; and there is high level of awareness on implications of disability acts towards inclusive PA and Sports among SNPs in University of Ilorin. Therefore, the study recommended that specially designed sports facilities and other resources should be provided by the school authority and charity organisations to facilitate PA and sports participation for health promotion and rehabilitation.